C(sp2)–H functionalization in non-aromatic azomethine-based heterocycles. Issue 2 (7th October 2020) - Akulov, Alexey A.; Varaksin, Mikhail V.; Mampuys, Pieter; Charushin, Valery N.; Chupakhin, Oleg N.; Maes, Bert U. W.
Abstract : This review highlights the advances in the direct C(sp 2 )–H functionalization of cyclic aldimines, aldohydrazones, and aldonitrones since 2008. Abstract : Direct C(sp 2 )–H functionalization of the endocyclic azomethine and aldonitrone moieties in non-aromatic azaheterocycles has established itself as a promising methodology over the last decade. Transition metal-catalyzed cross-coupling reactions, α-metalation–electrophile quenching protocols, and (metal-free) nucleophilic substitution of hydrogen reactions (SN H ) are the major routes applied on cyclic imines and their derivatives. In this overview, we show the tangible progress made in this area during the period from 2008 to 2020.